Columba's Island : Iona from Past to Present - MacArthur, Mairi (Edinburgh University Press, 2022)
For the Gaels it is I Chaluim Chille. From here, Colum Cille - or St Columba - and his successors spread their Christian mission throughout Scotland and beyond. An early king of Dál Riata was consecrated here, and later the mighty Lords of the Isles brought their chieftains for burial on Iona's soil. In more recent times the island was the setting for the Iona Community, a radical experiment in church witness and worship.Living alongside these events, and often in their shadow, there has also been a local community. This is the first book about Iona to span the ages, tracing the population from prehistoric times to the present era. From the inhabitants of an iron-age fort to the medieval village clustered beside the Cathedral walls, and onwards right up to the men and women who worked the land and sea through two World Wars, it takes a fresh look at Columba's Island. And it seeks to delve behind the layers of myth and mystery which have built up around this historic place and the lives of its people, great and small, throughout the centuries.